Behavioral Indicators of Drug Carrying in Open Spaces. (February 2019) - Meehan, Nathan; McClary, Michael; Garinther, Alexander
This article identifies and describes a set of behavioral indicators associated with illegal drug carrying in public spaces. Through the use of focus group data, our research documents and translates the visual search techniques that veteran law enforcement and drugs experts report using in their work. Here, we catalogue these findings into 10 overarching categories, and discuss how each indicator may be incorporated into an officer's visual search. Knowledge of these indicators, when combined with proper training and an understanding of a public space, can help law enforcement identify persons who may be carrying drugs. The ability to identify drug-carrying individuals facilitates the interdiction and apprehension of offenders, and also protects the civil rights and liberties of the law-abiding public.